Diseases of the nose, throat and ear : for practitioners and students - Turner, A. Logan (Arthur Logan), 1865-1939 (John Wright & Sons, 1936)
Diseases of the Nose, Throat and Ear: For Practitioners and Students, Fourth Edition provides information pertinent to the fundamental aspects of the diseases of the ear, nose, and throat. This book discusses allergy and its allied conditions. Organized into six sections encompassing 41 chapters, this edition begins with an overview of anatomical structure of the nose. This text then explores the various processes of examination of the cavities of the nose, pharynx, larynx, and ear. Other chapters consider inference with phonation, which is one of the most common symptoms in affections of the.